Identification of the TMV Replicase Sequence That Activates the N Gene-Mediated Hypersensitive Response - Hal S. Padgett; Yuichiro Watanabe; Roger N. Beachy (Molecular Plant-Microbe Interactions, 1997)
The N gene-mediated hypersensitive response (HR) in tobacco provides a high degree of resistance against most tobamoviruses by halting the progress of infection at the site of inoculation. A previous report indicated a role for the 126/183-kDa replicase in induction of the HR in tobacco containing the N gene (H. S. Padgett and R. N. Beachy, Plant Cell 5:577-586, 1993). Chimeric virus genomes were constructed in which the genes encoding the 126/183-kDa proteins of the HR-eliciting pathogen, tobacco mosaic virus (TMV), and the resistance breaking tobamovirus, Ob, were exchanged. Inoculation of the chimeric viruses to leaves of Nicotiana tabacum cv. Xanthi NN confirmed that either the replicase protein of TMV or its mRNA was responsible for induction of HR. An expression vector based on the Ob virus was used to express fragments of various replicase genes. With this approach, it was determined that the HR is caused by a portion of the replicase protein extending from amino acid 692 to 1116. Consistent with this result, Ob mutants that induce the HR on NN tobacco were found to carry mutations within the same portion of the replicase gene. The N gene-mediated HR is inactive at high temperatures, yet these mutants were able to overcome the HR at significantly lower temperatures than could TMV, indicating that the temperature sensitivity of the N gene response is manifested at the level of interaction between the virus and the defense response mechanism.